False Hadith, Identity, and Contestation of Thought: The Analysis of hadith on the division of Muhammad's Ummah in the Historical Dimension - Miski, Miski (Madania: Jurnal Kajian Keislaman, 2021)
This study positioning false hadiths (mawdhû‘) as historical documents and historical data, not just past information, which is considered wrong and must be avoided. The hadith used as the object of study was the Prophet's words, "All will enter Heaven except the al-Zanâdiqa Group." The main issue that we want to explore is what matters behind the hadith's emergence. Using a historical approach, normative analysis, and historical, this study shows: first, that the hadith is considered a false hadith, both from its sanad and matan aspects. However, the assessment of these two aspects does not co-occur. Second, the diction of "al-Zanâdiqa," which is interpreted with the al-Qadariyyahsect, appeared in the verbal form before the 4th century AH / 10 AD as a form of resistance to the al-Qadariyyahsect. However, since the 4th century AH/ 10th AD, the hadith has entered into various hadith literature as a form of resistance to the hadith's existence as a false hadith. Third, in the 6th century AH/ 12th AD, this hadith became a new discourse, namely as an authentic hadith but without the addition of the diction of "al-Qadariyyah." In the 10th century AH/ 16th AD or the 12th century AH/ 18th AD, and in the 14th century AH/ 20th AD, it also appeared to the public. This finding also shows that hadith was one of the authoritative tools to corner groups considered the opposite of the mainstream, causing contestation and discourse shiftKajian ini dimaksudkan untuk memosisikan hadis palsu sebagai dokumen dan data sejarah, tidak sekedar informasi masa lalu yang pasti salah. Hadis yang dijadikan objek kajian adalah hadis yang berbunyi “Semua akan Masuk Surga kecuali Golongan al-Zanâdiqa.” Persoalan utama yang ingin dieksplorasi adalah peristiwa apa yang berada di balik kemunculan hadis tersebut. Dengan menggunakan pendekatan sejarah; analisis normatif dan historis, kajian ini menunjukkan: pertama, hadis tersebut dinilai sebagai hadis palsu, baik dari aspek sanad maupun matannya. Meskipun, penilaian terhadap dua aspek ini tidak terjadi secara simultan. Kedua, diksi “al-Zanâdiqa” yang ditafsirkan dengan golongan al-Qadariyyah, muncul dalam bentuk verbal sebelum abad ke 4 H/10 M sebagai bentuk resistansi terhadap golongan al-Qadariyyah. Namun, sejak abad ke 4 H/10 M, hadis tersebut sudah masuk ke dalam berbagai literatur hadis sebagai bentuk resistansi terhadap keberadaan hadis itu sebagai hadis palsu. Ketiga, pada abad ke-6 H/12 M, hadis ini menjadi diskursus baru yakni sebagai hadis sahih namun tanpa tambahan diksi “al-Qadariyyah.” Pada abad ke 10 H/16 M atau abad ke 12 H/18 M juga muncul ke khalayak. Demikian pula pada abad 14 H/20 M kembali muncul–di samping diskursus yang memang sudah eksis sebelumnya. Temuan ini juga menunjukkan, di masa itu, hadis menjadi salah satu alat yang otoritatif untuk menyudutkan golongan yang dinilai berseberangan dengan golongan arus utama; melahirkan kontestasi dan pergeseran diskursus.